Development Design Ma'had Al-Jamiah in State Islamic Religious College in Indonesia - Priatna, Tedi; Khana, Muhammad Amar (IJoIS: Indonesian Journal of Islamic Studies, 2025)
This study aims to analyse the Development Design of Ma'had Al-Jami’ah in State Islamic Religious Universities in Indonesia (Case Study on Ma'had Al-Jamiah UIN Maulana Malik Ibrahim Malang and UIN Sunan Gunung Djati Bandung). The type of research used in this study is field research. With primary and secondary data sources. Using a qualitative research approach. Data analysis is carried out inductively, starting from data reduction, presentation, and conclusion drawing/verification. The results of this study highlight the importance of a holistic approach in managing Ma'had al-Jami'ah to produce quality graduates and contribute to Islamic education in Indonesia. At the input stage, Islamic boarding schools must meet the needs of students and universities by strengthening religious understanding, academic and non-academic skills, and adaptability to global challenges, supported by quality teaching staff, adequate facilities, and sustainable funding. The development process includes the preparation of an integrative curriculum between religion and general sciences, technology-based management, and developing superior activities such as tahfiz, yellow book studies, and entrepreneurship. The result is graduates with religious, academic, and social competencies who can become change agents and realise institutional sustainability through a good reputation.